Isolation of nitric oxide synthetase, a calmodulin-requiring enzyme. - Bredt, D S (1990)
Nitric oxide mediates vascular relaxing effects of endothelial cells, cytotoxic actions of macrophages and neutrophils, and influences of excitatory amino acids on cerebellar cyclic GMP. Its enzymatic formation from arginine by a soluble enzyme associated with stoichiometric production of citrulline requires NADPH and Ca2+. We show that nitric oxide synthetase activity requires calmodulin. Utilizing a 2',5'-ADP affinity column eluted with NADPH, we have purified nitric oxide synthetase 6000-fold to homogeneity from rat cerebellum. The purified enzyme migrates as a single 150-kDa band on SDS/PAGE, and the native enzyme appears to be a monomer.